Ternate Sultanate Palace Museum as a Media for History Learning - Acim Acim; Gazali Far-Far (STKIP Singkawang, 2021)
The purpose of this study was to determine the collection of historical relics at the Ternate Sultanate Museum/Palace, and their use as a historical learning medium. While the problems studied in the research are: (1) what are the collections of historical relics in the museum / Sultanate of Ternate Palace? (2) how to use it as a historical learning media?. The research method used is library research, where the required materials/data are obtained from the library, both books, documents, journals, encyclopedias, articles and others. Based on the results of the research, the museum/Palace of the Sultanate of Ternate collects various historical relics, and can be used as a medium for learning history on the history of the entry of Islam, and the arrival of Europeans in the Archipelago.